Socio- Economic Analysis of Fadama Farmers in Akure South Local Government Area of Ondo State, Nigeria - Folayan, J. A (American Journal of Humanities and Social Sciences, 2013)
<!--[if gte mso 9]> <![endif]--> This study examined the socio economic analysis of Fadama farmers in Akure South Local Government Area of Ondo State. The data were collected through structured questionnaire from a sample of 100 respondents drawn from ten (10) purposively selected communities from the local Government area. The data collected was analyzed by use of percentage, frequency, descriptive statistics, gross – margin and regression analysis. The findings from the study showed that. Majority 100% of the respondents had one constraint or the other with the suggestion of new technology, adequate funding and improved input supply and provision of infrastructure to cushion their problems. The gross margin per annum of fadama farmer was N254, 000 with N21, 166.6 per month showed that fadama farming was profitable in the area of study. The regression analysis result showed that increase in the values of marital status, household size, level of that education, experience and farm size imply an will increase fadama farmers productivity while an increase in age and gender will reduce the rate of Fadama farming productivity in the study area. It was recommended that education of farmers should be encouraged while soft loan, agricultural inputs and research assistance be provided by Government. The implication findings from this study were that men were more actively involved in Fadama farming than the female, enough profit was generated to sustain the family while cooperative society was a predominant source of capital in fadama farming in the study area. <!--[if gte mso 9]> Normal 0 false false false EN-US X-NONE AR-SA <![endif]--><!--[if gte mso 9]> <![endif]--><!--[if gte mso 10]> <mce:style><! /* Style Definitions */ table.MsoNormalTable {mso-style-name:"Table Normal"; mso-tstyle-rowband-size:0; mso-tstyle-colband-size:0; mso-style-noshow:yes; mso-style-priority:99; mso-style-parent:""; mso-padding-alt:0in 5.4pt 0in 5.4pt; mso-para-margin:0in; mso-para-margin-bottom:.0001pt; text-align:justify; mso-pagination:widow-orphan; font-size:11.0pt; font-family:"Calibri","sans-serif"; mso-ascii-font-family:Calibri; mso-ascii-theme-font:minor-latin; mso-hansi-font-family:Calibri; mso-hansi-theme-font:minor-latin;} --> <!--[endif] -->